Influencing factors of suicidal ideation in lung cancer patients in Midland China: A mixed-method study - Yu, Ting; Hu, Deying; Jiang, Yan; Wang, Cong; Liu, Shanshan (Frontiers in Psychiatry, 2023)
The suicide risk of patients with lung cancer is higher than that of patients with other cancers. However, as China is a large country for lung cancer, there are no relevant reports on lung cancer suicides. This study aimed to investigate the prevalence of suicidal ideation and explore its influencing factors in patients with lung cancer. In this cross-sectional study, 366 patients with lung cancer were surveyed. Of these, eight with lung cancer and suicidal ideation were selected for in-depth interviews. A total of 22.68% of patients with lung cancer reported suicidal ideation. Sex, cancer stage, number of uncomfortable symptoms, and satisfaction with treatment were independently associated with suicidal ideation. This qualitative study found that the experience of suicidal ideation in patients with lung cancer includes physiological (heavy burden of symptoms), psychological (bad mood, thwarted belongingness, perceived burdensomeness, and stigma), and social factors (high economic pressure and negative life events). These findings suggest that there should be a routine to screen and assess suicidal ideation among patients with lung cancer and that related mental health and suicide prevention education should be conducted.